2012
DOI: 10.1161/hypertensionaha.111.182170
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally Active Syncytial Aggregates in the Maternal Circulation May Contribute to Circulating Soluble Fms-Like Tyrosine Kinase 1 in Preeclampsia

Abstract: The cardinal manifestations of the pregnancy-specific disorder preeclampsia, new-onset hypertension and proteinuria that resolve with placental delivery, have been linked to an extracellular protein made by the placenta, sFlt1 (soluble fms-like tyrosine kinase 1), that injures the maternal vasculature. However, the mechanisms by which sFlt1, which is heavily matrix-bound, gains access to the systemic circulation remain unclear. Here we report that the preeclamptic placenta’s outermost layer, the syncytiotropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 46 publications
3
102
2
1
Order By: Relevance
“…39 Although placenta is the major source of sFlt1 production, immunohistochemistry studies have suggested that syncytial knots (degenerating syncytiotrophoblast tissue) in the placenta is the major site of sFlt1 production. 40,41 These syncytial knots easily detach from the syncytiotrophoblast, resulting in free, multinucleated aggregates (50-to 150-μm diameter) that are loaded with sFlt1 protein and mRNA, and are capable of de novo gene transcription and translation. 40,42 Other studies using autopsy material have suggested that shed syncytial knots may contribute to circulating sFlt1 in preeclampsia.…”
Section: Biology Of Antiangiogenic State In Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation
“…39 Although placenta is the major source of sFlt1 production, immunohistochemistry studies have suggested that syncytial knots (degenerating syncytiotrophoblast tissue) in the placenta is the major site of sFlt1 production. 40,41 These syncytial knots easily detach from the syncytiotrophoblast, resulting in free, multinucleated aggregates (50-to 150-μm diameter) that are loaded with sFlt1 protein and mRNA, and are capable of de novo gene transcription and translation. 40,42 Other studies using autopsy material have suggested that shed syncytial knots may contribute to circulating sFlt1 in preeclampsia.…”
Section: Biology Of Antiangiogenic State In Preeclampsiamentioning
confidence: 99%
“…40,41 These syncytial knots easily detach from the syncytiotrophoblast, resulting in free, multinucleated aggregates (50-to 150-μm diameter) that are loaded with sFlt1 protein and mRNA, and are capable of de novo gene transcription and translation. 40,42 Other studies using autopsy material have suggested that shed syncytial knots may contribute to circulating sFlt1 in preeclampsia. 43 Because these synytial microparticles are of fetal origin, this process of syncytial microparticle shedding may lead to chimerism, as fetal cells can be retained in the maternal blood and organs for decades after delivery.…”
Section: Biology Of Antiangiogenic State In Preeclampsiamentioning
confidence: 99%
“…93 This disorder develops during pregnancy, and the rapid and complete recovery after childbirth indicates that the placenta has a pivotal role in the pathogenesis of this disease. 94 Although the aetiology of pre-eclampsia is still subject to debate, the basic pathologic event in pre-eclampsia is an injury to the vascular endothelium 95 that is mediated by OS from increased placental ROS or decreased antioxidant activity. 96 Consequently, trophoblastic invasion to the spiral arteries is inhibited that limits the spiral artery remodelling to the decidual portions and the myometrial segments of the arteries remain narrow and contractile.…”
mentioning
confidence: 99%
“…Transitory local hypoxic/hyperoxic changes exceedingly erode the syncytiotrophoblast and shed debris into maternal circulation. These debris release vasoactive substances such as endothelin 1 (55) and antiangiogenic factors (notably sFLT-1 and sENG), thus contributing to the maternal systemic endothelial injury.…”
mentioning
confidence: 99%